Does finance solve the supply chain financing problem?. Issue 5 (8th August 2016) - Caniato, Federico; Gelsomino, Luca Mattia; Perego, Alessandro; Ronchi, Stefano
Abstract : Purpose: Recently, in response to the credit crunch and the increased costs of financing, new solutions for supporting the financial management of supply chains, known as supply chain finance (SCF), have been developed. They exploit the strengths of supply chain links to optimise working capital. The purpose of this paper is to provide a reference framework that links together the objectives leading to the adoption of SCF solutions and several moderating variables. Design/methodology/approach: This paper adopts a multiple case study methodology, analysing 14 cases of the application of SCF solutions among Italian companies. Findings: The main findings are the identification of the different objectives leading to the adoption of SCF; the analysis of the impact of moderating variables (the level of inter- and intra-firm collaboration, the level of the trade process digitalisation and the bargaining power and financial strength of the leading firm) on SCF adoption; and the formulation of a reference framework supporting the effective adoption of SCF solutions. Research limitations/implications: This contribution is exploratory in nature; theory-testing contributions should be the focus of further research. Also, the sample is limited to Italian companies. Finally, the service provider's point of view has been marginally taken into consideration in this study. Originality/value: The article addresses the need for more empirical research on SCF. It provides a reference framework focused on the objectives and moderating variables leading to effective SCF adoption, providing a theory-building contribution on the general topic of SCF and on the specific topic of the adoption process of different SCF solutions.